EFFECT OF RIBLETS AND SUCTION ON A FLAT PLATE TURBULENT BOUNDARY LAYER - Oyewola, M. O. (Revista de Engenharia Térmica, 2006)
This work presents hot-wire measurements in a flat plate turbulent boundary layer, subjected to the combination of riblets and suction. The suction is applied through a porous strip for a range of suction rates. The effect of riblets and suction has been quantified through the measurements of mean velocity and Reynolds stresses downstream of the suction strip on the riblets surface. The results of the mean velocity and Reynolds stresses indicate that there is no significant change in the distributions of riblets and smooth wall. However, there exist some changes with the combination of suction and riblets relative to the smooth surface. These changes arise from the interference of suction with the mechanism of the layer. The results suggest that riblets may not alter the effect suction has on the boundary layer structures.